Predominant location of coronary artery atherosclerosis in the left anterior descending artery. The impact of septal perforators and the myocardial bridging effect - Wasilewski, Jarosław; Niedziela, Jacek; Osadnik, Tadeusz; Duszańska, Agata; Sraga, Wojciech; Desperak, Piotr; Myga-Porosiło, Jolanta; Jackowska, Zuzanna; Nowakowski, Andrzej; Głowacki, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : Coronary artery atherosclerosis presents characteristic patterns of plaque distribution despite systemic exposure to risk factors. We hypothesized that local hemodynamic forces induced by the systolic compression of intramuscular septal perforators could be involved in atherosclerotic processes in the left anterior descending artery (LAD) adjacent to the septal perforators’ origin. Therefore we studied the spatial distribution of atherosclerosis in coronary arteries, especially in relation to the septal perforators’ origin. Material and methods : 64-slice computed tomography angiography was performed in 309 consecutive patients (92 male and 217 female) with a mean age of 59.9 years. Spatial plaque distribution in the LAD was analyzed in relation to the septal perforators’ origin. Additionally, plaque distribution throughout the coronary artery tree is discussed. Results : The coronary calcium score (CCS) was positive in 164 patients (53.1%). In subjects with a CCS > 0, calcifications were more frequent in the LAD (n = 150, 91.5%) compared with the right coronary artery (RCA) (n = 94, 57.3%), circumflex branch (CX) (n = 76, 46.3%) or the left main stem (n = 42, 25.6%) (p < 0.001). Total CCS was higher in the LAD at 46.1 (IQR: 104.2) and RCA at 34.1 (IQR: 90.7) than in the CX at 16.8 (IQR: 61.3) (p = 0.007). In patients with calcifications restricted to a single vessel (n = 54), the most frequently affected artery was the LAD (n = 42, 77.8%). In patients with lesions limited to the LAD, the plaque was located mostly (n = 37, 88.1%) adjacent to the septal perforators’ origin. Conclusions : We demonstrated that coronary calcifications are most frequently located in the LAD in proximity to the septal branch origin. A possible explanation for this phenomenon could be the dynamic compression of the tunneled septal branches, which may result in disturbed blood flow in the adjacent LAD segment (milking effect).